Diaries of Court Ladies of Old Japan - Omori, Annie Shepley; Izumi Shikibu; Murasaki Shikibu; Sugawara no Takasue no Musume, 1008-; Doi, Kochi, 1886-1979 (Salt Lake City, UT : Project Gutenberg, 2014)
"Diaries of Court Ladies of Old Japan" translated by Annie Shepley Omori and Kochi Doi is a historical collection of personal diaries written during the early 11th century. This work presents an intimate glimpse into the lives of Japanese noblewomen during the Heian Period, showcasing their thoughts, experiences, and interactions within the court. The diaries reveal the complex emotional landscape of these women, particularly regarding love, loss, and societal expectations, portrayed through nuanced poetry and prose. At the start of the "Sarashina Diary," the narrator reflects on her upbringing in a distant province and her yearning to read romances, particularly tales about the romantic Shining Prince Genji. She describes her emotional farewell to her childhood home as she journeys to the royal city, capturing the varying landscapes and her emotions throughout the voyage. The narrative reveals her vulnerability, as she experiences homesickness and a profound desire for connection, depicted through her poignant poetry and relationships with family members. The opening sets the stage for a coming-of-age tale imbued with dreams, aspirations, and the trials of a sensitive soul in a world filled with beauty and sorrow. (This is an automatically generated summary.)
The Sarashina diary -- The diary of Murasaki Shikibu -- The diary of Izumi Shikubu.
Release date is 2014-10-19
Produced by Madeleine Fournier and Marc D'Hooghe (Images generously made available by
Keywords: Japanese diaries -- Women authors -- Translations into English; Japan -- Court and courtiers